Diagnostic limitations of clinical case definitions of pertussis in infants and children with severe lower respiratory tract infection. - Rudzani Muloiwa; Mark P Nicol; Gregory D Hussey; Heather J Zar (PLoS ONE)
Introduction Diagnosis of pertussis is challenging especially in infants. Most low and middle-income countries (LMIC) lack resources for laboratory confirmation, relying largely on clinical diagnosis alone for both case management and surveillance. This necessitates robust clinical case definitions. Objectives This study assesses the accuracy of clinical case definitions with and without lymphocytosis in diagnosing pertussis in children with severe lower respiratory tract infection (LRTI) in a LMIC setting. Methods Children hospitalized with severe LRTI in a South African hospital were prospectively enrolled and evaluated for pertussis using PCR on respiratory samples. Clinical signs and differential white cell counts were recorded. Sensitivity and specificity of pertussis clinical diagnosis using WHO and Global Pertussis Initiative (GPI) criteria; and with addition of lymphocytosis were assessed with PCR as the reference standard. Results 458 children <10 years were enrolled. Bordetella pertussis infection was confirmed in 32 (7.0%). For WHO criteria, sensitivity was 78.1% (95% CI 60.7-89.2%) and specificity 15.5% (95% CI 12.4-19.3%); for GPI sensitivity was 34.4% (95% CI 20.1-52.1) and specificity 64.8% (95% CI 60.1-69.2%). Area under the curve (AUC) on receiver operating character (ROC) analysis was 0.58 (95% CI 0.46-0.70 for WHO criteria, and 0.72 (95% CI 0.56-0.88) for GPI with highest likelihood ratios of 5.33 and 4.42 respectively. Diagnostic accuracy was highest between five and seven days of symptoms for both criteria. Lymphocytosis had sensitivity of 31.3% (95% CI 17.5-49.3%) and specificity of 70.7% (95% CI 66.1-74.8%) and showed a marginal impact on improving clinical criteria. Conclusion Clinical criteria lack accuracy for diagnosis and surveillance of pertussis. Non-outbreak settings should consider shorter durations in clinical criteria. New recommendations still fall short of what is required for a viable clinical screening test which means the need to improve access to laboratory diagnostic support remains crucial.